1992
DOI: 10.1128/aem.58.8.2559-2564.1992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibacterial agents on in vitro ovine ruminal biotransformation of the hepatotoxic pyrrolizidine alkaloid jacobine

Abstract: Ingestion of pyrrolizidine alkaloids, naturally occurring plant toxins, causes illness and death in a number of animal species. Senecio jacobaea pyrrolizidine alkaloids cause significant economic losses due to livestock poisoning, particularly in the Pacific Northwest. Some sheep are resistant to pyrrolizidine alkaloid poisoning, because ovine ruminal biotransformation detoxifies free pyrrolizidine alkaloids in digesta. Antibacterial agents modify ruminal fermentation. Pretreatment with antibacterial agents ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In 1992 these early studies were followed by a number of publications from Oregon State University (College of Veterinary Medicine). These showed that gram-positive bacteria were most likely critical members for the degradation of jacobine in the rumen of sheep (Wachenheim et al, 1992a), and that when measuring in vitro degradation of Jacobaea vulgaris PAs in bovine (cattle), ovine (sheep), and caprine (goat) rumen contents average rates of around 3, 19 and 26 micrograms/ml per hour, respectively were found. The rumen contents used were from animals that had not recently been exposed to PAs.…”
Section: Ruminantsmentioning
confidence: 93%
See 1 more Smart Citation
“…In 1992 these early studies were followed by a number of publications from Oregon State University (College of Veterinary Medicine). These showed that gram-positive bacteria were most likely critical members for the degradation of jacobine in the rumen of sheep (Wachenheim et al, 1992a), and that when measuring in vitro degradation of Jacobaea vulgaris PAs in bovine (cattle), ovine (sheep), and caprine (goat) rumen contents average rates of around 3, 19 and 26 micrograms/ml per hour, respectively were found. The rumen contents used were from animals that had not recently been exposed to PAs.…”
Section: Ruminantsmentioning
confidence: 93%
“…Beside the already described pathways, PA detoxification mediated by bacterial flora in the rumen may be an important contribution to the observed resistance of sheep to PA toxicity (Wachenheim et al, 1992a;Anjos et al, 2010), but evidently not occurring to the same extent in other more susceptible ruminants such as cattle (Cheeke, 1988;Wachenheim et al, 1992b) or in horses (Cheeke, 1988). Further details are given in Section 7.4.…”
Section: Metabolismmentioning
confidence: 99%
“…Clinical symptoms of ruminant PA intoxication include loss of appetite, diarrhoea and depression [ 28 ]. Livestock losses were reported in the United States due to livestock grazing PA containing plants of Senecio jacobaea (tansy ragwort) [ 29 ] while PA intoxication of poultry, cattle, horses and pigs in Australia has identified PA containing plants Heliotropium europaeum (European heliotrope) and Echium plantagineum (Paterson’s curse) to be responsible [ 167 , 168 , 169 , 170 , 171 ]. Calves fed with S. jacobaea in doses of 1.3 kg/day (3 mg/kg bodyweight (bw) PA) resulted in megalocytosis after 182 days [ 32 ].…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“…Consistently, rabbits with high activity of N-glucuronidation are resistant to PA poisoning (Mattocks 1986), while rats, mice, and dogs with negligible N-glucuronidation activity are susceptible to PA toxicity (Huan et al 1998b). Apart from the species variance of PA intoxication mediated by hepatic enzymes, ruminal microbiota has been suggested as an important contributor for PA detoxification in sheep, while other ruminants such as cattle and horses are susceptible to PA intoxication (Anjos et al 2010;Cheeke 1988;Wachenheim et al 1992). Further studies are needed to unravel the functional roles of gut flora in PA metabolism.…”
Section: Species and Gender Differences In Pa Metabolismmentioning
confidence: 99%